Analysis of various maximum power point tracking strategies for a synchronous generator based wind turbine system - Dawson, Grant Stephen (2018)
The rapid growth of wind turbine systems within the past two decades has been very significant within the renewable energy sector. The increasing number of wind farms has led to a driving interest in discovering new challenges and creating new technologies for these wind turbines. The aim of this project is to research both the electrical and mechanical components of a wind turbine system including the drive train and generator. A literature review was carried out to explore the fundamental equations that converts the kinetic energy of the wind to the output electrical energy that is supplied to the grid. The first section investigated was the mechanical shaft which is very important within the drive train model. It was found that stiffness and internal damping are both vital when designing the drive train shaft. If any of these parameters are too high then it can lead to a reduction in output power and damage to the turbine. A wind turbine and drive train model was then analysed and simulated in Matlab, investigating the relationship between the fundamental equations and the wind turbine components. This resulted in many different output waveforms being mathematically analysed to determine the relationship between key parameters such as rotor speed, mechanical power and electromagnetic torque. A study between the different types of generators that are used within wind turbine systems was also carried out which found that a DFIG is the most common type with around 70% of wind turbines using this type of generator. DFIG have many advantages such as operating at synchronous and variable speed as well as easily being controlled with the use of converters by changing the voltage. A DFIG is however more complex than a PMSG which have higher efficiencies, require lower maintenance and cost less to manufacture. A simulation model was then set up for a PMSM with varying parameters of input torque and load. It was found that by increasing the load resistance increases the current, voltage and also the settling time. When the input torque increased, the output electromagnetic torque also increased along with the generator rotor speed. This leads to an increased output electrical power from the generator.